Role of psychological factors on the performance of elite soccer players - Mohamad Razali, Abdullah; Rabiu Muazu, Musa; Ahmad Bisyri Husin Musawi, Maliki (Editura Universitatii din Pitesti, 2016)
The application of psychological strategies to improve performance in sports has developed significantly over the past few decades. Nowadays, coaches are beginning to realize the significance of psychological factors in enhancing player’s performance. However, determining the magnitude of the impact of psychological factors in a soccer game may assist in developing player’s capacity to perform. This study aims to determine the role of psychological factors on the performance of elite soccer players. We enrolled elite players competing in the Malaysian Super League with a mean age of ± 25 years. Psychological constructs questionnaire proposed by PSIS-R-5 was administered to the players, and the scores of each player were recorded. We analyzed the performances of the players for eight weeks. A standard multiple regression was performed at p ≤ 0.05 alpha levels with the motivation, confidence, anxiety control, mental preparation, team emphasis, concentration and cognition as (IVs) to predict performance (DV). A Noteworthy regression equation was found (F (7, 12) = 15.109, P < .001) with R² of .90 indicating that the model has approximately accounted for the total of 90% variability. Although correlations were found.57, .14, .88, .71, .65, .76 and .42 respectively between the (IVs) and the (DV), none of the (IVs) is a predictor of the (DV) (P > 0.05). Based on the results of this analysis, it is tempting to conclude that, despite the correlation between psychological factors and performance, psychological factors alone could not determine the performance of elite soccer players.